An Empirical Investigation of Static Compression Tests on Mortar Composite Materials with Different Proportions of Fly Ash - Faisal Amri Tanjung; Siahaan, Muhammad Yusuf Rahmansyah; Rakhmad Arief Siregar (Universitas Medan Area, 2024)
The engineering of composite mortar materials presents substantial economic advantages and significant potential for advancement in the construction sector, particularly through applications such as plant vases, coral transplant media, seawalls, wall decorations, bricks, paving blocks, and acoustic panels. The use of fly ash, an industrial byproduct, can facilitate the production of high-quality materials in alignment with the government’s circular economy initiatives. This study employs a mortar mixture with a 1:1 ratio combined with varying compositions of fly ash at 10%, 30%, and 50%, utilizing an experimental testing approach that includes a static load compression test. The purpose of the compression testing apparatus is to ascertain the compressive strength characteristics and the mass percentage of the materials. The findings revealed that the maximum compressive strength achieved with 10% fly ash was 34.07 MPa; however, variations in the fly ash composition led to a reduction in the material's toughness properties by 10.42% and 16.53%, respectively. The recorded compressive strength values comply with the quality standards set forth in SNI 03-0691-1996 for paving blocks classified as type B quality. Furthermore, the variations in composition positively influenced the mass percentage, with considerable increases of 66.67% and 45.33% corresponding to the differing fly ash compositions.